Zonulin as marker of pregnancy induced hypertension: a case control study - Ahmed Tijani Bawah; Henry Tornyi; Mohammed Mustapha Seini; Lincoln Toamsoma Ngambire; Francis Agyemang Yeboah (BMC, 2020)
Abstract Background Zonulin has been implicated in many metabolic disorders including hypertension and obesity. However, there is insufficient information about the involvement of zonulin in pregnancy induced hypertension (PIH) which comprises preeclampsia (PE) and gestational hypertension (GH). This study was therefore aimed at finding the level of this biochemical marker of regulation of tight junctions among women with PIH. Methods A total of 88 women with PIH and 60 age and body mass index (BMI) matched healthy pregnant women controls were enrolled. Blood pressure at 11-13 weeks and after 20 weeks of gestation, body mass index (BMI) in addition to serum Zonulin levels and lipid profile were compared between the groups. Student's t-test was used for comparisons of the mean between the two groups. Correlation analyses were performed using Pearson's correlation and binary logistic regression was used to evaluate the factors associated with PIH. Results Zonulin level was significantly higher in the participants with PIH as compared to the normal pregnant controls 56.81 ± 7.72 ng/ml vs 40.4 ± 8.60 ng/ml p < 0.0001 and had strong positive correlation with PIH (OR = 1.805; CI1.139-1.275; p < 0.0001). However, the association between first trimester lipids and PIH was weak. Conclusion The results showed a strong positive correlation between zonulin and PIH, thus changes in intestinal permeability occur in early stages of pregnancy and may be involved in the pathogenesis of PIH.